The Pengaruh Struktur Kepemilikan, Sales growth dan Struktur modal terhadap Nilai Perusahaan - Meliana, Nila Ade; Azzahra, Khoirunnisa (JURNAL AKUNTANSI BARELANG, 2024)
This research aims to provide emprical evidence that there is an influence of the Managerial Ownership Structure, Institusional Ownership Structure, Sales Growth and Capital Structure on Company Value in preoperties and real estate sector companes listed on the Indonesia Stock Exchange for the 2018 – 2022 period. The number of research samples was 18 companies in the properties and real estate sector based on the purposive sampling method. The methode used in multiple linear regression, descriptive statistical test, panel data regression model analysis, the selected model selection rest is the Random Effect Model (REM), classical assumption test, multiple linear test and hypothesis testing with the help of e-views version 12 statistical data processing. The result of this research show that simultaneousy Managerial Ownership Structure, Institusional Ownership Structure, Sales Growth and Capital Structure have influence Company Value. Partially state that the Managerial Ownership Structure has an effect on Campany Value. The Institusional Ownership Structure has no effect on Company Value. Institusional Ownership Structure has no effect on Company Value. Sales Growth has no effect on Company Value, and the Capital Structure variable has no effect on Company Value.